Nonlinear finite element analysis of solids and structures - Borst, René de.; Crisfield, M. A. (Chichester, West Sussex, United Kingdom : Wiley, 2012)
"The Finite Element Method (FEM) is a powerful technique originally developed for numerical solution of complex problems in structural mechanics, and it remains the method of choice for complex systems"--
Front Matter -- Basic Concepts and Solution Techniques. Preliminaries -- Non-linear Finite Element Analysis -- Geometrically Non-linear Analysis -- Solution Techniques in Quasi-Static Analysis -- Solution Techniques for Non-linear Dynamics -- Material Non-Linearities. Damage Mechanics -- Plasticity -- Time-dependent Material Models -- Structural Elements. Beams and Arches -- Plates and Shells -- Large Strains. Hyperelasticity -- Large-strain Elasto-plasticity -- Advanced Discretisation Concepts. Interfaces and Discontinuities -- Meshless and Partition-of-unity Methods -- Isogeometric Finite Element Analysis -- Index.
Revised edition of: Non-linear finite element analysis of solids and structures / M.A. Crisfield. c1991-c1997. (2 v.).
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Structural analysis (Engineering) -- Data processing; Finite element method -- Data processing; TECHNOLOGY & ENGINEERING -- Drafting & Mechanical Drawing; Finite element method -- Data processing; Structural analysis (Engineering) -- Data processing; Finite element method -- Data processing; Structural analysis (Engineering) -- Data processing; Finite element method - Data processing; TECHNOLOGY & ENGINEERING / Drafting & Mechanical Drawing; Engineering; Civil engineering; Electronic books; Electronic books